The Positive Fictional Principle After the Implementation of The Job Creation Law: A Prophetic Legal Paradigm - Pranoto, Edi; Sudarmanto, Kukuh (Magister of Law, Faculty of Law, University of Mataram, 2023)
The positive fictitious principle in the Law No. 11 of 2020 concerning Job Creation (CK Law) exists to facilitate investment and simplify licensing. However, the provisions in the CK Law, which exclude the role of the Administrative Court in fictitious applications have the potential to cause injustice and legal uncertainty in society. That research focuses on examining the positive fictitious principle's existence after the CK Law's enactment in the paradigm of prophetic law. The paradigm of prophetic regulation was chosen in this study as an effort to explore the theological (divine) and human dimensions in positive fictitious formulations as in CK Law. This research is a normative legal type of research with a concept and statutory approach. The results of the study confirm that in terms of the three aspects of prophetic law, namely transcendence, liberation, and humanization, the provisions of the CK Law, which no longer involve the role of the Administrative Court and have not issued Presidential Regulations regarding positive fiction can cause uncertainty and injustice in society. That makes the substance of the prophetic law in the positive fictitious provisions in the CK Law not be realized optimally. Orientation based on the prophetic legal paradigm in regulating the positive fictitious principle after regulation in the CK Law, according to the author, can be done by revising the positive fictitious provisions in the CK Law by returning the competence of the State Administrative Court.